y*4+y*7+y*9=40300
x*4+x*7+x*9=40300
x * 4 + x * 7 + x * 9 = 40300
x * ( 4 + 7 + 9 ) = 40300
x * 20 = 40300
x = 40300 : 20
x = 2015
x*4+x*7+x*9=40300
suy ra x*(4+7+9)=40300
suy ra x*20=40300
suy ra x=40300:20
suy ra x=2015
vậy x=2015
X x 4 + X x 7 + X x 9 = 40 300
X x ( 4 + 7 + 9 ) = 40 300
X x 20 = 40 300
X = 40 300 : 20
X = 2015
x*4+x*7+x*9=40300
X x 4 + X x 7 + X x 9 = 40300
=> X x ( 4 + 7 + 9 ) = 40300
=> X x 20 = 40300
=> X = 40300 : 20
=> X = 2015
Nhớ tick mik nha !!!
40 300 : ( 4 + 7 + 9 ) = 2015
=> x = 2015
Tìm x, biết:x*4+x*7+x*9=40300
Ta có : x . 4 + x . 7 + x . 9 = 40300
=> 20 . x = 40300
=> x = 40300 : 20
=> x = 2015
X x 4 + X x 7 + X x 9 =40300
X x 4 + X x 7 + X x 9 = 40300
X x (4 + 7 + 9) = 40300
X x 20 = 40300
X = 40300 : 20 = 2015
Xx4+Xx7+Xx9=40300
Xx(4+7+9)=40300
Xx20=40300
X=40300:20
X=2015
tìm x biết x * 4 + x * 7 + x 9 = 40300
X x 4 + X x 7 + X x 9 = 40300
X x ( 4 + 9 + 7 ) = 40300
X x 20 = 40300
X = 40300 : 20
X = 2015
Mọi người li-ke mik nhé !!!
x * 4 + x * 7 + x * 9 =40300
x * ( 4 +7 +9 ) = 40300
x * 20 = 40300
x = 40300 : 20
x =2015
tick nhé
x*4+x*7+x*9=40300
(x*x*x)x(4+7+9)=40300
3xx20=40300
3x=40300:20
3x=2015
x=2015:3
x=671,6666667
X x 4 + X x 7 + X x 9 = 40300
X x 4 + X x 7 + X x 9 = 40300
X x ( 4 + 7 + 9) = 40300
X x 20 = 40300
X = 40300 : 20
X = 2015
Vậy X = 2015
\(x\cdot4+x\cdot7+x\cdot9=40300\)
\(x\cdot\left(4+7+9\right)=403000\)
\(x\cdot20=40300\)
\(x=40300:20\)
\(x=2015\)
\(x\cdot4+x\cdot7+x\cdot9=40300\)
\(x\cdot\left(4+7+9\right)=403000\)
\(x\cdot20=40300\)
\(x=40300:20\)
\(x=2015\)
X x 4 + X x 7 + X x 9 = 40300
Tim X
X x 4 + X x 7 + X x 9 = 40300
X x (4 + 7 + 9) = 40300
X x 20 = 40300
X = 40300 : 20
X = 2015
E+x^(4)*y^(4)+x^(5)*y^(5)+x^(6)*y^(6)+x^(7)*y^(7)+x^(8)*y^(8)+x^(9)*y^(9)+x^(10)*y^(10) tại x=-1, y=1
E = x^(4)*y^(4)+x^(5)*y^(5)+x^(6)*y^(6)+x^(7)*y^(7)+x^(8)*y^(8)+x^(9)*y^(9)+x^(10)*y^(10) tại x=-1, y=1 nha
TÌM Y BIẾT:
a) y x 4/3= 16/9
b) (y-1/2)+0,5=3/4
c) 4/5-2/5 x y=0,2
d) (y+3/4)x5/7=10/9
e) y : 5/4=9/5+1/2
f) y x 1/2+3/2x y=4/5
a, y \(\times\) \(\dfrac{4}{3}\) = \(\dfrac{16}{9}\)
y = \(\dfrac{16}{9}\) : \(\dfrac{4}{3}\)
y = \(\dfrac{4}{3}\)
b, ( y - \(\dfrac{1}{2}\)) + 0,5 = \(\dfrac{3}{4}\)
y - 0,5 + 0,5 = \(\dfrac{3}{4}\)
y = \(\dfrac{3}{4}\)
c, \(\dfrac{4}{5}-\dfrac{2}{5}y\) = 0,2
0,8 - 0,4y = 0,2
0,4y = 0,8 - 0,2
0,4y = 0,6
y = 1,5
d, (y + \(\dfrac{3}{4}\)) \(\times\) \(\dfrac{5}{7}\) = \(\dfrac{10}{9}\)
y + \(\dfrac{3}{4}\) = \(\dfrac{10}{9}\) : \(\dfrac{5}{7}\)
y + \(\dfrac{3}{4}\) = \(\dfrac{14}{9}\)
y = \(\dfrac{14}{9}\) - \(\dfrac{3}{4}\)
y = \(\dfrac{29}{36}\)
e, y : \(\dfrac{5}{4}\) = \(\dfrac{9}{5}\) + \(\dfrac{1}{2}\)
y : \(\dfrac{5}{4}\) = \(\dfrac{23}{10}\)
y = \(\dfrac{23}{10}\)
y = \(\dfrac{23}{8}\)
f, y \(\times\) \(\dfrac{1}{2}\) + \(\dfrac{3}{2}\) \(\times\) y = \(\dfrac{4}{5}\)
y \(\times\) ( \(\dfrac{1}{2}+\dfrac{3}{2}\)) = \(\dfrac{4}{5}\)
2y = \(\dfrac{4}{5}\)
y = \(\dfrac{2}{5}\)